PhD: The Amazing Journey - Muhammad Ashraf, Fauzi; Cheng, Jack Kie; Puteri Fadzline, Muhamad Tamyez (Penerbit UMP, 2020)
Why do a PhD? Every PhD candidate has their own reason to pursue a PhD. Be it for the thirst of uncovering new knowledge, to discover new boundaries, to develop new skills or to go beyond one’s personal limit. Regardless of the motivation, the ultimate end is the same for all. That is, the bestowed of Doctor of Philosophy degree. However, no two candidates have the same experience, as the doctoral voyage is unique for each candidate. Every candidate has their own story to tell and each of them have different sceneries accompanying them throughout their PhD journey. This book compiles the amazing journey of nineteen successful PhD candidates. Nineteen different candidates, nineteen different experiences. Each story is a personal story, a personal PhD memoir. The editors handpicked stories from both local and oversea university graduates. All are equally poised, unique and refreshing, some with a twist or two, while some with sarcastic humour. This book is a great companion for PhD candidates who are either just embarking their PhD voyage or in the midst of their PhD journey. It is also a great sneak peek for PhD candidate-to-be, who are curious on how does it feel to do a PhD. Surely, in any manner, the narratives in this book are relatable. It is hoped that this book inspires and provides strength and motivation to the readers, to persistently carry on walking towards their ultimate goal, the Doctor of Philosophy degree